CSU meat school, no. 5: Meat cutting for different markets - Sullins, Martha, speaker; Thistlethwaite, Rebecca, speaker; Delmore, Bob, speaker; Colorado State University. Extension, producer (Colorado State University. Libraries, 2019)
Meat School overview: December 4 - Processing: meat cutting instructions & methods for different markets.
Meat cutting for different markets
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Animal industry; Meat industry and trade; Packing-houses; Slaughtering and slaughter-houses